A novel inflammatory role for platelets in sickle cell disease. (17th November 2015) - Davila, Jennifer; Manwani, Deepa; Vasovic, Ljiljana; Avanzi, Mauro; Uehlinger, Joan; Ireland, Karen; Mitchell, W. Beau
Abstract: The severe pain, ischemia and organ damage that characterizes sickle cell disease (SCD) is caused by vaso-occlusion, which is the blockage of blood vessels by heterotypic aggregates of sickled erythrocytes and other cells. Vaso-occlusion is also a vasculopathy involving endothelial cell dysfunction, leukocyte activation, platelet activation and chronic inflammation resulting in the multiple adhesive interactions between cellular elements. Since platelets mediate inflammation as well as thrombosis via release of pro- and anti-inflammatory molecules, we hypothesized that platelets may play an active inflammatory role in SCD by secreting increased amounts of cytokines. Since platelets have been shown to contain mRNA and actively produce proteins, we also hypothesized that SCD platelets may contain increased cytokine mRNA. In this cross-sectional study, we sought to compare both the quantity of cytokines secreted and the cytokine mRNA content, between SCD and control platelets. We measured the secretion of Th1, Th2, and Th17-related cytokines from platelets in a cohort of SCD patients. We simultaneously measured platelet mRNA levels of those cytokines. Platelets from SCD patients secreted increased quantities of IL-1β, sCD40L, and IL-6 compared to controls. Secretion was increased in patients with alloantibodies. Additionally, mRNA of those cytokines was increased in SCD platelets. Platelets from sickle cell patients secrete increased amounts of inflammatory cytokines, and contain increased cytokine mRNA. These findings suggest a novel immunological role for platelets in SCD vasculopathy, in addition to their thrombotic role, and strengthen the rationale for the use of anti-platelet therapy in SCD.